Evaluation of Scrum Implementation and Recommendation Improvement in Software Development: a Case Study of Logistic Company XYZ - Tanjung, Muhammad Fadly; Purwandari, Betty; Fedinansyah, Alex; Trisnawaty, Ni Wayan (The Indonesian Journal of Computer Science, 2024)
PT XYZ provides a digital platform for the national logistics ecosystem and is connected to a global network. PT XYZ applies Agile as a project management methodology so that each team member can focus on continuous improvement and delivering value to customers. The framework used is Scrum during software development to complete work in Agile. However, there are problems during software development, such as failing to meet the targeted deliverables. This research evaluates the implementation of Scrum in PT XYZ and provides recommendations for improving the software development process using Scrum Evaluation Metrics based on Scrum Guide 2020 and Essentials Scrum. The research utilized mixed methods, combining quantitative data collection through questionnaires with qualitative methods involving interviews with Scrum Master and stakeholders, followed by a review of company documents. The result was processed using the Agile Maturity Model's Key Process Area (KPA) rating. The research shows that overall, the KPA rating value of 87.39% is interpreted as Fully Achieved. Recommendations for improvement focused on 27 recommendations for 61 practices that were not Fully Achieved, with high priority given to 15 recommendations. This evaluation and recommendation aim to improve the implementation of Scrum in PT XYZ and overcome the problem of backlog targets not being achieved in the Fulfillment squad.